Caring for Fiṭra: A Point of Encounter Between Islām and Montessori’s Conception of the Child’s Inner Potential - Colonello, Paola (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
Drawing on ethnographic fieldwork conducted by the author in the Iranian provinces of Ostān-e Tehrān, Ostān-e Fārs, Ostān-e Bušehr, and Ostān-e Sīstān va Balūcistān and a noteworthy interview with a prominent Āyatollāh of the theocratic government, this article examines the environmental pressures acting upon fiṭra with the aim of highlighting both the educational opportunity to harness its potential and—as a distinctive contribution—the significance it may hold within Maria Montessori’s spiritual sensibility. As research results reveal, inspired by the thought of the Italian pedagogist, for just over a decade a few pioneering Iranian educational psychologists have been assisting Muslim teachers in shifting their focus toward children’s intrinsic motivation and respect for individual learning needs. Despite longstanding reluctance from the theocratic government, the syncretic approaches they have been promoting may prove effective in caring for the child’s fiṭra. In the article, Islamic psychology and Montessori’s perspective are juxtaposed, and tensions between educational needs and state concerns regarding the socio-political implications of such adoption are critically explored. The author concludes by reflecting on how adopting ideas from a different cultural milieu and adapting them to local educational contexts, far from implying submission to external intellectual hegemony, may unexpectedly yield positive learning outcomes.